One Health research ethics review processes in African countries: Challenges and opportunities - Kuastros M. Belaynehe; Joseph M. Nguta; Melanie Lopez; Jinjian Mu; Dónal O'Mathúna; Getnet Yimer; Andréia G. Arruda (One Health, 2024)
One Health research has gained attention over the past few decades due to its potential to improve health challenges across the globe. However, obtaining ethics approvals for timely implementation of One Health research is a challenge in some contexts. Our study was undertaken to describe various challenges faced by researchers, research ethics committees (RECs) and members of regulatory bodies in Africa. An online survey was conducted between March and June 2021. The effect of predictors, including respondents' role (e.g., REC member, regulator and/or One Health researcher), sex, education, age, and country, on the perception of challenges and opportunities when conducting and reviewing One Health research, was investigated using multivariable linear regression models. Participants with different roles did not perceive any of the examined challenges differently during review of One Health-related research; but female participants (p = 0.026) and those with ten or more years of experience (p = 0.0325) perceived insufficient One Health knowledge as less of a challenge. Professional role was an important predictor (p = 0.025) for the perception of the establishment of a mandatory One Health review system. Respondents with multiple roles perceived the creation of ad hoc committees for review of One Health research under emergency situations to be less important (p = 0.02); and REC members perceived the creation of such committees to be less feasible (p = 0.0697). Our study showed that perceptions of the importance and feasibility of opportunities for improvement of One Health research ethics review under emergency and non-emergency situations varied across professional roles. This emphasizes the need to consider such improvement strategies; and the need for continuous and timely evaluation for improvement of ethics review of One Health and emergency research in Africa.